Catalisadores Pt/Al2O3 e CeO2/Pt/Al2O3 aplicados à reação deslocamento gás-água: efeito da composição nas propriedades estruturais e catalíticas - Borges, Laís Reis (Universidade Federal de São Carlos, 2018)
Alumina-supported platinum catalysts were synthesized via conventional impregnation varying the metal contents (0.3 to 2% Pt; 6 to 20% Ce, m / m) and the Pt precursors (H2PtCl6 and [Pt(NH3)4] (NO3)2), were evaluated for the structure-activity relationship in the water gas shift reaction (WGS). The results of the X-ray absorption spectroscopy analysis for the Pt/Al2O3 catalysts indicated different average sizes of metal platinum nanoparticles supported on alumina (0.7 and 1.4nm) as a function of the metal precursor, and an increase in the oxygen under the surface and/or under the metal-support interface with decreasing platinum/nanoparticle size. However, the inside and surface electron density has not been modified as indicated by the same Pt-Pt (2.75Å) and Pt-O (2.00Å) bond distances for all of the catalysts. Theoretical mechanical-quantum calculations indicated an insensitivity of the bond distances in clusters of Pt greater than 13 atoms with the addition of oxygen under the surface, suggesting that the synthesized samples are larger than this one, corroborating with the analysis of transmission electron microscopy. Infrared spectroscopy with CO adsorption (FTIR-CO) showed a distribution of metallic and slightly oxidized platinum species under the surface, and an increase of Pt0 sites of low coordination with the platinum content due to a lower coverage of the oxygen. These sites of low coordination presented a greater thermal stability of CO. As for the activity in the WGS reaction of the Pt/Al2O3 catalysts, the reaction frequency (TOF) decreased (0.5 to 0.2 s-1) with increasing platinum content (0.3 to 2% Pt), suggesting that fractions of the active sites under the samples with high platinum content, calculated by FTIR-CO, do not participate in the reaction due to the strong adsorption of CO. The addition of ceria on the Pt/Al2O3 catalysts decreased the number of Pt-Pt coordination and increased Pt-O, indicating a greater stabilization of the nanoparticles (average size ≤ 1nm) and a strong interaction of the Pt particles with CeOx species. However, in spite of the structural changes, there was no change in the surface electronic density of the Pt nanoparticles. The increase in the activity (TOF) of up to 10 times with the cerium content in relation to the non-promoted catalysts suggested that the activity was controlled by sites of Pt-O-Ce interface, which modified the reaction path. The presence of Cl under the promoted samples affected the redox properties of ceria, making it difficult to transfer oxygen and thus to increase the activity. Therefore, it can be affirmed that the structural properties allowed to identify the active sites that determine the catalytic performance in the WGS reaction.
Keywords: Catalisadores heterogêneos; Reação deslocamento gás-água; Nanopartículas de platina; Céria; Espectroscopia de absorção de raios X; Heterogeneous catalysts; Gas-water displacement reaction; Platinum nanoparticles; X-ray absorption spectroscopy; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA